Profil Kontrol Glikemik Antidiabetik pada Pasien DM Tipe 2 dengan Sirosis Hati - Emy Oktaviani; Lusi Indriani; Haryanti Wulandari (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2022)
Diabetes mellitus (DM) is a metabolic syndrome with multi-etiology characterized by chronic hyperglycemia. DM can cause a variety of complications, one of which is impaired liver function. The use of antidiabetics needs to get more attention because most antidiabetics are metabolized in the heart. This study aims to determine the control of antidiabetic glycemic, the relationship of antidiabetic types with effectiveness, as well as factors related to glycemic control in type 2 DM patients with liver cirrhosis.  This research was conducted in June-July at Fatmawati Central General Hospital with cross sectional design and data retrieval period of 2014-2019 conducted retrospectively. The observation parameters of glucose control in this study were current blood sugar (GDS). Of the 106 patients who met the inclusion criteria, it was seen that the use of insulin aspart single in 34 patients showed good glycemic control followed by the use of combination insulin glargine-aspart in 25 patients. The results of the Chi-square analysis showed that there was no significant relationship between the type of antidiabetic on glycemic control (p-value = 0,159). However, the results of the Chi-square test showed that there was a significant relationship between the severity of liver cirrhosis and glycemic control (p-value=0,021) and gender was another factor that also showed a significant relationship to glycemic control (p-value=0,042). The use of insulin aspart alone or in combination with insulin glargine is the best in controlling blood sugar levels while in T2DM patients with liver cirrhosis based on this study.